2006
DOI: 10.1530/rep.1.00588
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calpain and Rho-kinase inhibitors on the acrosome reaction and motility of fowl spermatozoa in vitro

Abstract: inhibitor of protein phosphatases, which also initiates sperm motility at 40 8C. The addition of PD 150606 did not reduce the ATP concentrations of intact spermatozoa, nor the motility of demembranated spermatozoa. Immunoblot analysis of sperm extract using a polyclonal antibody against calpain 12 revealed a cross-reacting protein of approximately 80 kDa. These results suggest that Rho-kinase is not involved in the regulation of the acrosome reaction or of motility in fowl spermatozoa. In contrast, calpain app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Ca 2C influx from the extracellular medium to the cytosol through voltage channels is believed to be the first event that initiates the successive signaling pathways required for the acrosome exocytotic secretory response. The concomitant need of two factors, IPVL components and Ca 2C , for the in vitro induction of the chicken acrosome reaction has already been reported by different authors (Horrocks et al 2000, Ashizawa et al 2004, 2006a, 2006b). However, the present study showed that a small percentage of acrosome-reacted spermatozoa may be obtained with the presence of Ca 2C without IPVL in the BPSE and DMEM media, and in the three media studied after the addition of Ca 2C ionophore.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Ca 2C influx from the extracellular medium to the cytosol through voltage channels is believed to be the first event that initiates the successive signaling pathways required for the acrosome exocytotic secretory response. The concomitant need of two factors, IPVL components and Ca 2C , for the in vitro induction of the chicken acrosome reaction has already been reported by different authors (Horrocks et al 2000, Ashizawa et al 2004, 2006a, 2006b). However, the present study showed that a small percentage of acrosome-reacted spermatozoa may be obtained with the presence of Ca 2C without IPVL in the BPSE and DMEM media, and in the three media studied after the addition of Ca 2C ionophore.…”
Section: Discussionmentioning
confidence: 71%
“…Okamura & Nishiyama (1978) described the ultrastructure of the acrosome reaction when spermatozoa are in contact to the IPVL of the ovulated oocyte. Horrocks et al (2000) suggested that the IPVL inducers of acrosome reaction could be N-linked oligosaccharides with terminal N-acetyl-glucosamine residues, while Ashizawa et al (2004Ashizawa et al ( , 2006aAshizawa et al ( , 2006b) started to describe the signaling pathways involved in the chicken acrosome reaction and Rabbani et al (2006Rabbani et al ( , 2007 suggested the involvement of sperm-associated bodies in the interaction of spermatozoa and IPVL. However, the understanding of the factors involved in the induction of the acrosome reaction is still very incomplete, despite its importance for the understanding of the process of fertilization itself and the need to counteract induction of the acrosome reaction when it occurs spontaneously after in vitro storage for example.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ashizawa et al [17] showed that PKC may contribute to inhibition of the reaction. In addition, protein phosphatases type 1 and/or type 2A and protein phosphatase type 2B have been suggested to be involved in the regulation of the acrosome reaction in the chicken, because specific inhibition activities of these phosphatases significantly stimulate the reaction [17][18][19]. However, the potential involvement of kinases, such as MAPKs (MAPK3/1 and MAPK14), PKA, and PIK3, has not been investigated to date.…”
Section: Introductionmentioning
confidence: 99%
“…In presence of PVL the ability of sperm to perform the AR was not different (P>0.05) in fresh semen than thawed semen using BPSE diluent, however with Lake diluent the ability of sperm to perform the AR was lower (P<0.05) after thawed. Some studies have reported that cryopreservation impairs the ability of sperm to undergo an AR due to the reduced production of cAMP, lack of mobilization of Ca 2+ , or oxidative stress and changes in the proportion of cholesterol and phospholipids in the membranes before the AR (Ashizawa et al 2006). The percentage of sperm that underwent an AR was always higher (P<0.05) when they were induced with PVL than the percentage that underwent an AR without PVL.…”
Section: Resultsmentioning
confidence: 95%